Front Matter the 8th AIC 2018 - the 8th AIC 2018 on Social Sciences (Proceedings of AICS - Social Sciences, 2018)
Assalamualaikum Wa Rahmatullahi Wa Barakatuh,On behalf of the organizing committees, I would like to welcome all of you to Banda Aceh, Indonesia for the 8th Annual International Conference on Social Sciences as a part of the 2018 Annual International Conference (AIC) Syiah Kuala University. The AIC is an annual international conference carried out regularly by Syiah Kuala University since 2011. The past seven conferences held in the past seven years have achieved great success, making this series prestigious and influential to academicians, researchers, and practitioners.Under the theme of “Connecting the world through innovation and sustainable development“, this conference features a rich program, including Syiah Kuala University Innovation Expo 2018, a keynote speech delivered by Dr. Evan Lau from University Malaysia Sarawak, Malaysia, and our invited speaker, Dr. M. Shabri Abd. Majid from Syiah Kuala University, Indonesia. The 8th AIC on Social Sciences 2018 offers a special opportunity to bring together professors, researchers and scholars around the globe to deliver innovative research results and latest trends and development in the fields of social sciences.The selected papers in this conference will have the opportunities to be published in The International Journal of Language Studies (IJLS) (indexed in SciVerse SCOPUS), and Journal of Finance and Banking and Al Ta’lim Journal (both Nationally Accredited by the Ministry of Research, Technology and Higher Education/Ristek DIKTI). The conference has received 44 submitted papers from Indonesia, Germany, and Russia and have been accepted by the committees for presentation and to be included in the proceedings. These papers on various topics are divided into 10 parallel sessions at the conference. To all members of the organizing committees, the international scientific committees, the reviewers, and the collaboration partners, we would like to thank all of them for their tremendous efforts to organize this conference successfully. Dr. Heru FahleviGeneral Chair